Transient Solutions for a Pendulum Coupled to a DC Motor - Avanço, Rafael Henrique; Zanella, Danilo Antonio; de Jesus Arias Cantillo, Raibel; Cunha, Américo; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo (Springer Nature, 2024)
The present text analyzes the influence of the inductance and the rotor inertia on the dynamics of a pendulum vertically moved by a DC motor through a yoke-scotch mechanism. The analysis also includes the influence of the mass on the tip of the pendulum. Time histories for the position and speed of the pendulum are presented, and the phase portraits demonstrate the type of motion and the amplitudes. The motor speed is affected by the pendulum characterizing a nonideal excitation. The results point that amplitude and speed in the pendulum increase when the mass on the pendulum increases. A small influence of the rotor inertia is found, and no influence of the inductance is present in steady state regions. Higher values for the mass of the pendulum provokes a lower speed in the motor, larger values for the rotor inertia diminish the final speed of the motor, but the inductance does not affect the final speed of the DC motor in the present analysis.
Keywords: DC motor; Inductance; Nonideal vibrations; Pendulum